Effective optical and treatment zone analysis by means of cross-over differences after lenticule extraction - Hamed Haidari; Victor Derhartunian; Thomas Magnago; Maren-Christina Lengle; Samuel Arba-Mosquera (Heliyon)
Purpose: To determine the size of the effective optical and treatment zones after lenticule extraction procedures. Design: Retrospective case series. Methods: A fully automated method to determine the boundaries of the optical and treatment zones of a lenticule of tissue extracted from a cornea has been developed, in which the boundaries of the corrected area are derived from differences between post and preoperative maps of several corneal metrics by determining the smallest cross-over point along each semi-meridian. Results: The method has been applied to a pilot cohort of 84 eyes, clinical data showing average diameters of 6.56 ± 0.46 mm [5.25 to 7.51] and 8.49 ± 0.56 mm [6.58 to 9.52] for tangential anterior curvature and corneal thickness, respectively. Conclusions: The method provides a reliable and objective way to determine the size of a lenticule of tissue extracted from a cornea and it can be applied to any topo- or tomographic derived metric. Translational relevance: To determine the size of the effective optical and treatment zones after laser vision correction, a fully automated method was developed. The method is simple to implement and can be used to determine the actual size of a corneal correction and help titrating the planned size. The advantages of this algorithm over existing methods are its objectivity; automation; speed; resolution, accuracy and precision; the free-form boundary determination; and finally its support in determining centration and circularity.